Linking Alpha-Synuclein to the Actin Cytoskeleton: Consequences to Neuronal Function - Oliveira da Silva, Marina I.; Liz, Márcia A. (Frontiers in Cell and Developmental Biology, 2020)
Alpha-Synuclein (aSyn), a protein highly enriched in neurons where it preferentially localizes at the pre-synapse, has been in the spotlight because its intraneuronal aggregation is a central phenomenon in Parkinson’s disease. However, the consequences of aSyn accumulation to neuronal function are not fully understood. Considering the crucial role of actin on synaptic function and the fact that dysregulation of this cytoskeleton component is emerging in neurodegenerative disorders, the impact of aSyn on actin is a critical point to be addressed. In this review we explore the link between aSyn and actin and its significance for physiology and pathology. We discuss the relevance of aSyn-actin interaction for synaptic function and highlight the actin-depolymerizing protein cofilin-1 as a key player on aSyn-induced actin dysfunction in Parkinson’s disease.